2020
DOI: 10.1016/j.cell.2020.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Chromosome Removal after Cas9 Cleavage in Human Embryos

Abstract: The correction of disease-causing mutations in human embryos could reduce the burden of inherited genetic disorders in the fetus and newborn, and improve the efficiency of fertility treatments for couples with disease-causing mutations in lieu of embryo selection. Here we evaluate the repair outcomes of a Cas9-induced double-strand break (DSB) introduced on the paternal chromosome at the EYS locus, which carries a frame-shift mutation causing blindness.We show that the most common repair outcome is microhomolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
220
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(229 citation statements)
references
References 41 publications
8
220
0
1
Order By: Relevance
“…The simplicity, versatility and easy accessibility of CRISPR/Cas9 make it popular in the world. However, several recent studies conducted in human embryos have raised safety concerns about heritable genetic changes [6,7]. These studies revealed frequent loss and reshuffling of the targeted chromosome and heightened concerns surrounding the uncertain risk of CRISPR/Cas9 editing.…”
Section: Future Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…The simplicity, versatility and easy accessibility of CRISPR/Cas9 make it popular in the world. However, several recent studies conducted in human embryos have raised safety concerns about heritable genetic changes [6,7]. These studies revealed frequent loss and reshuffling of the targeted chromosome and heightened concerns surrounding the uncertain risk of CRISPR/Cas9 editing.…”
Section: Future Perspectivementioning
confidence: 99%
“…These studies revealed frequent loss and reshuffling of the targeted chromosome and heightened concerns surrounding the uncertain risk of CRISPR/Cas9 editing. They also raise the possibility that the phenotype after gene editing is due to chromosome loss, rather than homologous recombination-based repair [6,7]. Thus several improvements should be made in the near future.…”
Section: Future Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Off-target effects are the most common challenge for all genome editing technologies, and CRISPR/Cas9 is no exception even for its crown of precision and efficiency. Only 22 days after the 2020 Noble Prize was announced, Dr. Dieter Egli's laboratory published an article entitled "Allele-Specific Chromosome Removal after Cas9 Cleavage in Human Embryos" in Cell, emphasizing the significant risk of aneuploidy and other adverse genetic consequences resulting from CRISPR/Cas9 gene editing in early human embryos [7]. This article demonstrated that approximately half of Cas9-induced double-strand breaks (DSB) remained unrepaired after manipulation, followed by chromosomal losses and hemizygous indels after mitosis due to off-target effects in both alleles.…”
Section: Dear Editormentioning
confidence: 99%